Drug Related Problems Diabetic Nephropathy Patients in a Tertiary Hospital in Malaysia - Dika P. Destiani; Athirah Ghazali (Universitas Padjadjaran, 2016)
Patients with diabetic nephropathy (DN) are particularly vulnerable to drug related problems (DRPs) due to complex medication regimen and renal dysfunction. However, there was limited information regarding prevalence of DRPs among patients with DN in Malaysia. This research was conducted to determine the prevalence of DRPs among hospitalized patients with DN at tertiary hospital in Malaysia during June 2014-May 2015. This was a retrospective observational descriptive study that used patients medical records as data source. There were 104 subjects included in this study. The prevalence of DRPs among the included subjects was 74%. Most DRPs observed were from two categories, namely non-compliance to medication and adverse drug reactions (20.93% for both categories). These categories were followed by the category of unnecessary drugs (16.28%), too low dose (15.81%), inappropriate drugs (11.16%), untreated indication (10.23%) and too high dose (4.65%). Pharmacists are encouraged to perform comprehensive medication review to improve health outcomes and enhance patients safety. Keywords: Drug related problems, diabetic nephropathy, T2DM